Pengaruh Influencer Marketing, Kualitas Konten, dan Diskon Harga Terhadap Keputusan Pembelian Lozy Hijab dengan Self Control Sebagai Variabel Moderasi - Siti Aisyah; Afif Zaerofi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to test and analyze the influence of influencer marketing, content quality, and discounts on Lozy HIjab purchasing decisions moderated by self-control. The method in this study uses a causal quantitative method. The sampling technique in this study is the Non-Probability and Purposive sampling methods. The number of samples using the Slovin formula and there are 220 respondents. In this study, data was obtained from distributing online questionnaires. The data analysis technique uses the Partial Least Square Structural Equation Modeling (PLS-SEM) technique. The results of the study indicate that the variables of content quality and discounts have a positive and significant effect on purchasing decisions. While the influencer marketing variable has no effect on purchasing decisions. And self-control can significantly moderate the effect of discounts on purchasing decisions. Kaywords: Influencer marketing, content quality, price discount, self control, purchasing decision